Re-design of Portable Pedal Basins to Prevent the Spread of the Covid-19 Virus - Nuruddin Wahtu Eko Putro; Dede Zulrahman; Anis Siti Nurrohkayati (Procedia of Engineering and Life Science, 2021)
The process of spreading covid-19 is very fast and we must always be vigilant about this one outbreak. When the disease is transmitted so quickly by hand or direct contact. When crowding out we don't know where the disease came from or from who, so we have to keep our distance, wash our hands, wear a mask. Until now, the spread of the virus has increased more than in the previous year and the number of positives every day continues to increase, while various activities must continue to run so that people can remain productive and feel safe. Therefore, the purpose of implementing the re-design of the existing sink was made to re-create a portable pedal sink that was designed in the Autodesk Inventor application and updated on the cover of all sides of the sink so that it is tidier. The manufacturing process is more flexible and there are two sinks, right and left. For the sink work system, the system is stepped on so it is safer for us to use because it is without using hands. If you look at the public in general, they still use an ordinary sink so that the Mechanical Engineering Students of the Muhammadiyah University of East Kalimantan can design and design a pedal system sink or stepping system to make it easier for the prevention of Covid-19 in the city of Samarinda.